Efficient and Selectable Production of Reactive Species Using a Nanosecond Pulsed Discharge in Gas Bubbles in Liquid. Issue 3 (12th November 2015) - Dai, Xiujuan J.; Corr, Cormac S.; Ponraj, Sri B.; Maniruzzaman, Mohammad; Ambujakshan, Arun T.; Chen, Zhiqiang; Kviz, Ladge; Lovett, Robert; Rajmohan, Gayathri D.; de Celis, David R.; Wright, Marion L.; Lamb, Peter R.; et al.
Abstract : A plasma gas bubble‐in‐liquid method for high production of selectable reactive species using a nanosecond pulse generator has been developed. The gas of choice is fed through a hollow needle in a point‐to‐plate bubble discharge, enabling improved selection of reactive species. The increased interface reactions, between the gas‐plasma and water through bubbles, give higher productivity. H2 O2 was the predominant species produced using Ar plasma, while predominantly N O 3 − and NO2 were generated using air plasma, in good agreement with the observed emission spectra. This method has nearly 100% selectivity for H2 O2, with seven times higher production, and 92% selectivity for N O 3 −, with nearly twice the production, compared with a plasma above the water. Abstract : A plasma gas bubble‐in‐liquid, with chosen gas, method is described . The gas of choice enables improved selection of reactive species and increased interface reactions enable higher productivity. "Ar" plasma produces a high concentration of H2 O2, while "air" plasma produces high concentrations of N O 3 − and NO2 . The selectivity and productivity are much higher than with a plasma created above liquid.